PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI PERUMAHAN OBAMA PT. NAILAH ADI KURNIA SEI MENCIRIM MEDAN - Muhammad Fakhru Rizky Nasution; Hanifa - Yasin (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This study aimed to determine the effect of promotion and price to intentionto buy. Sample that observed were 100 respondent that interest and would buy theproduct. The result showed that promotion and price, partially andsimultaneously influence to intention to buy. Determinant coefficient showed that14,3% variation of intention to buy had influenced by promotion and price.